Analysis of Three-Dimensional Cell Migration in Dopamine-Modified Poly(aspartic acid)-Based Hydrogels - David Juriga; Eszter Eva Kalman; Krisztina Toth; Dora Barczikai; David Szöllősi; Anna Földes; Gabor Varga; Miklos Zrinyi; Angela Jedlovszky-Hajdu; Krisztina S. Nagy (Gels, 2022)
Several types of promising cell-based therapies for tissue regeneration have been developing worldwide. However, for successful therapeutical application of cells in this field, appropriate scaffolds are also required. Recently, the research for suitable scaffolds has been focusing on polymer hydrogels due to their similarity to the extracellular matrix. The main limitation regarding amino acid-based hydrogels is their difficult and expensive preparation, which can be avoided by using poly(aspartamide) (PASP)-based hydrogels. PASP-based materials can be chemically modified with various bioactive molecules for the final application purpose. In this study, dopamine containing PASP-based scaffolds is investigated, since dopamine influences several cell biological processes, such as adhesion, migration, proliferation, and differentiation, according to the literature. Periodontal ligament cells (PDLCs) of neuroectodermal origin and SH-SY5Y neuroblastoma cell line were used for the in vitro experiments. The chemical structure of the polymers and hydrogels was proved by 1H-NMR and FTIR spectroscopy. Scanning electron microscopical (SEM) images confirmed the suitable pore size range of the hydrogels for cell migration. Cell viability assay was carried out according to a standardized protocol using the WST-1 reagent. To visualize three-dimensional cell distribution in the hydrogel matrix, two-photon microscopy was used. According to our results, dopamine containing PASP gels can facilitate vertical cell penetration from the top of the hydrogel in the depth of around 4 cell layers (~150 μm). To quantify these observations, a detailed image analysis process was developed and firstly introduced in this paper.